Compressive Mechanical Properties and Micromechanical Characteristics of Warm and Ice-Rich Frozen Silt - Yugui Yang; Feng Gao; Yuanming Lai (Advances in Materials Science and Engineering)
It is recognized experimentally that the compressibility of warm and ice-rich frozen soil is remarkable under loading, which will cause a significant deformation and affect the stability of infrastructure constructed in cold region. In this paper, the real-time computerized tomography tests of warm and ice-rich frozen silt were carried out. The microstructure characteristics in the process of loading were studied, and the macromechanical behaviors were obtained at the same time. The test results showed that the stress-strain curve of warm and ice-rich frozen silt is sensitive to temperature; the peak stress was greatly enhanced with the decrease of temperature, and the section area increases with the increase of axial strain; the water content mainly decreases with the increase of axial strain at −1°C; the change of water content is not obvious at −2°C in the loading process. The density damage changes little at first and then increases with the further increase of axial strain.